Immobilization of phosphotungstate through doping in polypyrrole for supercapacitors. Issue 20 (25th April 2019) - Chang, Zhihan; Sang, Xiaoguang; Song, Yu; Sun, Xiaoqi; Liu, Xiao-Xia
Abstract : Immobilization of phosphotungstate is achieved through doping in polypyrrole. Owing to the proton sponge provided by polypyrrole, electrochemical stability in neutral solution is realized for phosphotungstate. Abstract : Immobilization of phosphotungstate is achieved through doping in polypyrrole via the electrochemical deposition of polypyrrole (PPy) in the presence of the phosphotungstate anions (PW12 ) on carbon nanotube film. Electrochemical stability in neutral solution is realized for PW12 in the prepared ECNT-PPy/5PW12, owing to the proton sponge provided by PPy. ECNT-PPy/5PW12 shows a high areal capacitance of 1300.0 mF cm −2 in LiCl solution at 1 mA cm −2 . ECNT-PPy/5PW12 also displays high rate capability and good cyclic stability due to the interaction of incorporated PW12 and the polymer matrix. ECNT-PPy/5PW12 can retain 78.6% and 92.0% of its capacitance with 40-fold current increase and after 10 000 galvanostatic charge/discharge cycles, respectively. An asymmetric supercapacitor with the ECNT-PPy/5PW12 anode and CNT-MnO2 cathode demonstrates high volumetric energy density (4.71 mW h cm −3 at 13.85 mW cm −3 ) and long cycle life (90.0% capacitance retention after 10 000 charge/discharge cycles).